The Effect of a Combination of Education and Spiritual Emotional Freedom Technique (SEFT) on Quality of Life Patients With Addressed Chronic Renal Failure Double Lumen Catheter - Herman Herman; Amin Samiasih; Ernawati Ernawati (Universitas Muhammadiyah Semarang, 2025)
Chronic kidney disease is a global health problem with increasing incidence and prevalence, long-term treatment, poor prognosis, and high treatment costs. Kidney failure patients face various complex issues, such as fluid and dietary restrictions, long-term treatments that result in loss of freedom, and dependence on healthcare services, affecting their quality of life. One effort to improve the quality of life in chronic kidney disease patients is the health education and Spiritual Emotional Freedom Technique (SEFT) program. SEFT is a psychological support technique focusing on holistic and spiritual well-being. This technique uses emotions and physical touch, often combined with prayer. The aim of this literature review is to determine the impact of the combination of education and the Spiritual Emotional Freedom Technique (SEFT) on the quality of life of chronic kidney disease patients with double-lumen catheter placement. This literature review was conducted by searching the results of publications in the Google Scholar, ProQuest, and Pubmed databases between 2019-2024 using the PRISMA method. The keywords used were self-management education AND spiritual emotional freedom technique AND quality of life AND CKD. The search for relevant articles included 13 sources that met the inclusion criteria. The conclusion is that the combination of education and the Spiritual Emotional Freedom Technique has an impact on the quality of life of chronic kidney disease patients with double-lumen catheter placement